"Poor brain development" in the global South? Challenging the science of early childhood interventions. (31st January 2023) - Scheidecker, Gabriel; Chaudhary, Nandita; Keller, Heidi; Mezzenzana, Francesca; Lancy, David F.
Abstract: Global Early Childhood Development (ECD)—an applied field with the aim to improve the "brain structure and function" of future generations in the global South—has moved to the center of international development. Global ECD rests heavily on evidence claims about widespread cognitive, social, and emotional deficits in the global South and the benefits of changing parenting practices in order to optimize early childhood development. We challenge these claims on the grounds that the leading ECD literature excludes research from anthropology, cultural psychology, and related fields that could provide crucial insights about childrearing and children's development in the targeted communities. We encourage anthropologists and other scholars with ethnographic expertise on childhood to critically engage with global ECD. To facilitate such an endeavor, this article sketches the history, scientific claims, and interventions of global ECD, points out the critical potential of ethnographic research, and suggests strategies to make ethnography more relevant. French translation of the abstract: Le développement cérébral est‐il déficient dans les pays du Sud ? Contester la scientificité des interventions précoses chez l'enfant Résumé: Le développement de la petite enfance (DPE) global — un domaine d'intervention dont l'objectif est d'améliorer "la structure et le fonctionnement cérébraux" des générations futures des pays du Sud — est aujourd'hui au coeur du développement international. Le DPE global affirme l'existence de déficits cognitifs, sociaux et émotionnels dans les pays du Sud, et promeut un changement des pratiques parentales afin d'optimiser le développement des enfants. Nous contestons ces affirmations: la littérature scientifique sur laquelle le DPE s'appuie ignore les recherche d'anthropologie, de psychologie culturelle et d'autres disciplines proches, concernant l'éducation des enfants et leur développement dans les communautés concernées. Nous encourageons les anthropologues et autres chercheurs ethnographes de l'enfance à entrer en débat avec le DPE global. Pour le permettre, cet article décrit l'histoire, les revendications scientifiques et les modes d'intervention de cette discipline. Il souligne le potentiel de la recherche ethnographique, et suggère des stratégies pour la rendre plus pertinente. Spanish translation of the abstract: ¿Desarrollo cerebral "deficiente" en el Sur Global? Criticando a la ciencia de las intervenciones en la primera infancia Resumen: El Desarrollo Global de la Primera Infancia (Early Childhood Development o ECD), eje central en los programas de desarrollo internacional, es un campo aplicado que busca mejorar la "estructura y función del cerebro" de las generaciones futuras en el Sur Global. En gran medida, el ECD postula que hay déficits cognitivos, sociales y emocionales entre los niños del Sur Global y sugiere optimizar el desarrollo de la primera infancia en los niños a través de ciertas prácticas de crianza. Argumentamos que, este paradigma excluye aportes académicos de antropología, psicología cultural y otros campos relacionados, sobre la crianza y el desarrollo de los niños en comunidades del Sur Global. En este artículo esbozamos el paradigma ECD según su historia, afirmaciones científicas e intervenciones, señalando, además, el potencial crítico de la investigación etnográfica. Por lo tanto, académicos con experiencia etnográfica en la niñez deben dialogar críticamente con este nuevo campo de intervención.